Analysing Metropolitan Municipal Water Services Delivery Performance in South Africa: A Comparative Assessment of Household Access, Water Quality, and Households’ Satisfaction - Abdulrasaq Ajadi Ishola; Tafadzwa Clementine Maramura; Trynos Gumbo (Journal of Digital Food, Energy & Water Systems, 2025)
This paper investigates the water service delivery performance of metropolitan municipalities in South Africa between 2022 and 2024. This enables an adequate understanding of the prevailing conditions of water service delivery in the metros and thus forms the basis for service enhancement intervention. Using a conceptual framework that combined principal-agent, equity, and public value theories, this study analyses a combination of secondary quantitative data on water service delivery performance across metropolitan municipalities in South Africa. The data was sourced from various government databases to pursue the study objectives of exploring water access, water quality, and households’ water service satisfaction. The findings revealed a significant disparity in the performance of the metros in water service delivery. While the City of Cape Town and Ekurhuleni demonstrated consistent water service excellence, Buffalo City, Nelson Mandela Bay, and Mangaung struggled with incessant water interruptions and declining water safety. Despite the robust water infrastructure status as reported in WIQI, systemic challenges, such as leaking water pipes and institutional inefficiency, undermine reliable water service delivery among metros in South Africa. This paper thus concludes that for South Africa to effec-tively address the persistent water service delivery challenges confronting it and efficiently achieve SDG 6 by 2030, there is the need for crucial investment in water management technology, establish water service delivery taskforce across metros, invest in wastewater treatment technologies, establish a national water management training institute to regular provide trainings to metro staff. Lastly, inter-metro best practices sharing must be entrenched, while a public database with updated water performance data must be made available to support water research. These recommendations emphasise inter-metro collaboration, techno-logical integration, and policy reforms to address systemic gaps and enhance public satisfaction with water service delivery.